Strategi Pembelajaran Pendidikan Agama Islam dalam Membentuk Kepribadian Disiplin Siswa SDIT Uswatun Hasanah - Rizqi Adi Pratama; Silmi Kaffah Meirani; Siti Nurhaliza; Daffa Ulima Azkia; Muhsin (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Education has a very strategic role in shaping the character and personality of students. this study aims to determine how the learning strategy of Islamic Religious Education is applied at SDIT Uswatun Hasanah Baleendah. this type of research is qualitative with a case study approach. The data sources of this research are primary data and secondary data, primary data is data taken directly from researchers to the source, without any intermediaries, namely data obtained directly through interviews and observations (observations), secondary data is data that is not in its own collection efforts such as documentation and collection techniques using observation, interviews, and documentation. Based on the results of the research that has been conducted, SDIT Uswatun Hasanah has carried out various Islamic learning strategies to shape the disciplinary character of students, the results of which are quite effective. Based on the results of this study, it can be concluded that the strategies made have worked well and can be developed again in the future. Keywords: Learning Strategy, Discipline Personality, and Monitoring